Contemporary paths: interviews with the visual artists Fabio Miguez and Manuel Caeiro (Revista Apotheke, 2025)
This article presents an excerpt from the doctoral research “Percursos Poéticos” (ECA/USP, 2017), featuring interviews with contemporary artists Fabio Miguez (São Paulo, 1962) and Manuel Caeiro (Évora, 1975). Conducted between 2014 and 2016 in São Paulo and Lisbon, the conversations address procedures, materials, and reflections on painting and the urban landscape. The project was supported by CAPES and the University of São Paulo’s Pro-Rectory of Culture and Extension. Rather than a comparative study, it highlights shared concerns regarding the city and artistic practice. The selection of these artists stems from the researcher’s own experience and affinities with their inquiries. The city, its landscapes, and the intellectual and material processes of artistic production are shared elements, with São Paulo, Lisbon, and other cities emerging as spaces of creation and experimentation.
Keywords: contemporary art; interview; urban landscape; creative processes; painting